Pengembangan dan Pemasaran UMKM Untuk Membangun Perekonomian Di Desa Mlorah Kabupaten Nganjuk - Nur Vita Dewan Tari; Nur Indah Fatmala; Neri Gareta Bintang Armevia; Kenneth Ephram Singarimbun; Rafael Octava Brilliante; Hendra Maulana (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
The development of Micro, Small and Medium Enterprises (MSMEs) is an effort carried out by KKN-T MBKM UPNVJT students from group 5 of Mlorah Village. Those who are trying to hold an MSME Bazaar are "KURMAH" which stands for Culinary Ramadhan Mlorah. This activity aims to empower the capabilities and competitiveness of MSMEs. The MSME Bazaar is also an instrument in realizing SDGs indicators. This activity was carried out to provide opportunities for MSME players to make their products better known to the wider community, thereby increasing the number of sales and helping improve the economy of MSME players in Mlorah Village. This activity uses the Participatory Action Research (PAR) method, an approach method that actively involves the community directly to find out where the problem is. From this activity we can observe directly and obtain results for the community such as; (1) insight and understanding regarding MSMEs, (2) improving the community's economy, (3) Creating an entrepreneurial spirit and high competitiveness, (4) Facilitating smooth communication between citizens and between MSME actors.